2016
DOI: 10.15171/ijhr.2016.13
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Microbiological Profile of Catheter Associated Urinary Tract Infections: A Survey in Secondary Care Hospital in Gaza Strip

Abstract: Background and Objectives People who seek healthcare are unable to tolerate the additional burden of acquiring a new infection. Healthcare associated infections (HAIs) are a major concern for healthcare management and frontlines to maximize patient safety. HAI is global health problem because of their seriousness, burden and costs to healthcare system. They also impose serious problems to safety of t patients. 1 In developing countries, the prevalence and incidence of HAIs varies between 5.7 to 19.1, and 1.7 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(19 reference statements)
2
0
0
Order By: Relevance
“…In this study, work experience/year of service showed statistically significant association with the occurrence of NSSI among nurses at p< 0.05. This finding is similar with studies conducted in three hospitals, Izmir, Turkey [2] , and secondary care hospital, Gaza Strip [11] showed that work experience/year of service had shown statistically significant association with the occurrence of NSSI among nurses at p< 0.05. It is due to the fact that as year of service increases, the chance of getting NSSI also increases.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, work experience/year of service showed statistically significant association with the occurrence of NSSI among nurses at p< 0.05. This finding is similar with studies conducted in three hospitals, Izmir, Turkey [2] , and secondary care hospital, Gaza Strip [11] showed that work experience/year of service had shown statistically significant association with the occurrence of NSSI among nurses at p< 0.05. It is due to the fact that as year of service increases, the chance of getting NSSI also increases.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, year of service >10 years was significantly associated with the occurrence of occupational exposure to sharp injuries among nurses at p<0.05. This finding was similar with studies conducted in three hospitals, Izmir, Turkey 18 and a secondary care hospital, Gaza Strip, 27 which showed that year of service had shown significant association with the occurrence of occupational exposure to sharp injuries among nurses at p<0.05. It might be due to the fact that as years of service increases, the chance of getting occupational exposure to sharp injuries also increases.…”
Section: Discussionsupporting
confidence: 90%